Baseline clinical characteristics of heart failure patients with reduced ejection fraction enrolled in the BUDAPEST‐CRT Upgrade trial. (22nd July 2022) - Merkely, Béla; Gellér, László; Zima, Endre; Osztheimer, István; Molnár, Levente; Földesi, Csaba; Duray, Gábor; Wranicz, Jerzy K.; Németh, Marianna; Goscinska‐Bis, Kinga; Hatala, Robert; Sághy, László; et al.
Abstract: Aims: The BUDAPEST‐CRT Upgrade study is the first prospective, randomized, multicentre clinical trial investigating the outcomes after cardiac resynchronization therapy (CRT) upgrade in heart failure (HF) patients with intermittent or permanent right ventricular (RV) pacing with wide paced QRS. This report describes the baseline clinical characteristics of the enrolled patients and compares them to cohorts from previous milestone CRT studies. Methods and results: This international multicentre randomized controlled trial investigates 360 patients having a pacemaker (PM) or implantable cardioverter defibrillator (ICD) device for at least 6 months prior to enrolment, reduced left ventricular ejection fraction (LVEF ≤35%), HF symptoms (New York Heart Association [NYHA] functional class II–IVa), wide paced QRS (>150 ms), and ≥20% of RV pacing burden without having a native left bundle branch block. At enrolment, the mean age of the patients was 73 ± 8 years; 89% were male, 97% were in NYHA class II/III functional class, and 56% had atrial fibrillation. Enrolled patients predominantly had conventional PM devices, with a mean RV pacing burden of 86%. Thus, this is a patient cohort with advanced HF, low baseline LVEF (25 ± 7%), high N‐terminal pro‐B‐type natriuretic peptide (NT‐proBNP) levels (2231 pg/ml [25th–75th percentile 1254–4309 pg/ml]), and frequent HF hospitalizations during the preceding 12 months (50%). Conclusion: When compared with prior CRT trial cohorts, the BUDAPEST‐CRT Upgrade study includes older patients with a strong male predominance and a high burden of atrial fibrillation and other comorbidities. Moreover, this cohort represents an advanced HF population with low LVEF, high NT‐proBNP, and frequent previous HF events. Clinical Trial Registration: ClinicalTrials.gov NCT02270840.